Estudio comparativo del comportamiento del consumo de los hogares en Ecuador, antes y durante la pandemia - Limones Lino, Daniel Arturo (2022)
The household consumption variable is fundamental in the country's finances since it represents a significant contribution to the Gross Domestic Product, and this is why it has been affected in recent years, based on this research: Comparative study of the behavior of Household Consumption in Ecuador, before and during the pandemic. We reviewed available material that provided information to be able to carry out and specify the theoretical framework. Then, a study of the household consumption variable by year is carried out, starting from 2018 until 2021. This variable has suffered positive and negative fluctuations during the years studied, it is important its analysis since the causes of its symptomatology are identified. The general objective is to comparatively analyze the consumption of households in Ecuador, before and during the pandemic, through a documentary study and field data that allow analyzing the behavior of this variable during the health emergency declared in the country. On the other hand, the methodology used in the research project is of a documentary, statistical and field type, with a mixed approach (quantitative - qualitative). The instruments used were interviews and official documents from related institutions; the first interview was directed to households in the northwest sector of Guayaquil and the second was directed to funeral homes, administrators, among others, in the northwest sector of Guayaquil, in order to analyze and compare the results of the statistical graphs and interviews, which demonstrate a correlation with the statistical table. Finally, the conclusions respond to the specific objectives and the recommendations contain suggestions for future studies in the field of consumption.